AMBULATORY ARTERIAL STIFFNESS MONITORING IN PATIENTS WITH ASTHMA - N. A. Karoli; O. T. Zarmanbetova; A. P. Rebrov (Архивъ внутренней медицины, 2019)
Cardiovascular disease is one of the major causes of death throughout the world. Early detection of target organ damage is important for more successful prevention of cardiovascular diseases and improvement of patient outcomes. One of these target organs is the vascular wall, and its damage consists in loss of elastic properties and increase in stiffness. Many studies have shown that the increasing stiffness of the vascular wall is an independent predictor of cardiovascular risk. Objective: To evaluate parameters of the ambulatory arterial stiffness monitoring in patients with bronchial asthma. Materials and methods. The study enrolled 119 patients with asthma. The group of control included 30 practically healthy volunteers comparable by gender and age with the patients of the main group. Each patient underwent ambulatory blood pressure and arterial stiffness monitoring using BPLab MnSDP-2 device (Petr Telegin, Russia). Results: In patients with asthma higher values of augmentation index, arterial stiffness index and pulse wave velocity in the aorta in comparison with patients of the control group, as well as violation of the 24-hour profile of arterial stiffness were noted. Conclusion. Patients with asthma demonstrated significantly increased arterial stiffness in comparison with control group.